Introduction: The ‘Labour Question’ in Contemporary Capitalism - Chhachhi, Amrita (Development and Change, 2014)
The recent upsurge in workers’ struggles globally has bought labour again to the forefront, despite predictions that the working class was no longer relevant as a force for social transformation. Neoliberal globalization, with the hypermobility of capital, has led to the emergence of new forms of flexible work/labour, the co-existence of old and new working classes, and an extreme rise in inequality, realigning class structures nationally and globally. Financialization has ushered in a new regime of accumulation and there is a deepening crisis of reproduction. Can a Marx plus Polanyi theoretical integration capture contemporary dynamics of capitalist globalization and the role of labour? What do the trajectories of such struggles in the South tell us about the limits and potentialities for a counter-capitalist movement? More crucially, is the route to full social citizenship entitlements still possible via employment (with its further extension universally), or is it to be reached by directly demanding citizenship rights, bypassing labour-based demands? How do recent collective actions express workers’ interests/identities as workers, citizens and consumers? What role is the state playing in responding/mediating/facilitating these struggles? The Introduction delineates some of these contentious issues which frame this Forum Debate. The contributors all offer different perspectives and critical insights on the connections between forms of labour, possibilities for action and organization, the relationship between labour struggles and social citizenship and the role of the state in contemporary capitalism. The conclusion reflects on some of the equally controversial proposed alternatives and argues for going beyond minimalism and for the imperative of radical rethinking to ensure dignified work and full social citizenship entitlements as part of a new social emancipatory political project.
Keywords: MARX, Karl, 1818-1883; capitalism; globalization; labor question; labour question; neoliberalism

Capital–Labour and State Dynamics in Export Horticulture in North-east Brazil - Selwyn, Ben (Development and Change, 2014)
This article argues for the primacy of class relations and struggles as determinants of developmental processes and outcomes, emphasizing the evolving, dialectical nature of these relations. It does so by providing a case study of export horticulture in North-east Brazil. It documents how the region's rural trade union has been able, through mobilizing its membership base, to achieve significant improvements in their livelihoods, pay and conditions. It also shows how the region's employers have responded to these gains by restructuring the labour force in order to attempt to fragment and weaken it. The article pays particular attention to the gender dynamics of class relations.
Keywords: Brazil; Polanyian approaches; class relations; development

The Global Development Crisis - Selwyn, Benjamin (John Wiley & Sons, 2014)
The central paradox of the contemporary world is the simultaneous presence of wealth on an unprecedented scale, and mass poverty. Liberal theory explains the relationship between capitalism and poverty as one based around the dichotomy of inclusion (into capitalism) vs exclusion (from capitalism). Within this discourse, the global capitalist system is portrayed as a sphere of economic dynamism and as a source of developmental opportunities for less developed countries and their populations. Development policy should, therefore, seek to integrate the poor into the global capitalist system. The Global Development Crisis challenges this way of thinking. Through an interrogation of some of the most important political economists of the last two centuries Friedrich List, Karl Marx, Leon Trotsky, Joseph Schumpeter, Alexander Gerschenkron, Karl Polanyi and Amarta Sen, Selwyn argues that class relations are the central cause of poverty and inequality, within and between countries. In contrast to much development thinking, which portrays ‘the poor’ as reliant upon benign assistance, this book advocates the concept of labour-centred development. Here ‘the poor’ are the global labouring classes, and their own collective actions and struggles constitute the basis of an alternative form of non-elitist, bottom-up human development.
Keywords: business & economics / development; economic development; embedded markets; political science / public policy / general; socialism

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Keywords: Great Transformation, The (Book); primitive societies